Sol-Gel Synthesis, Magnetic and Optical Properties of Co2+:Nd3+::2:1 molar ratio doped in SiO2 - Das, Bidhu Bhusan; Rao, Ruppa Govinda (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
Synthesis of Co2+:Nd3+::2:1 molar ratio doped SiO2 with Co2+ ions concentrations viz. 0.0004, 0.001,Â 0.002, 0.003, 0.004 moles in S1-S5, respectively are performed by sol-gel method. Observed values of the densities and the concentrations of the Co2+ ions in S1-S5 are found to be 2.26, 2.29, 2.37, 3.44, 2.49 g/cm3, and 1020 ions/g, respectively. Powder XRD results show the formation of amorphous SiO2 phase in the samples. DTA-TGA/DTG traces in the range 27-700 ËšC show no characteristic event in the samples. The IR peak in the range 412-418 cm-1 is ascribed to the asymmetric mode of the octahedral [NdO6/2]3- units. The peak around 440 cm-1 in S1-S5 is due to the Î½2-symmetric bending mode of the tetrahedral [SiO4/2]4- units. The weak IR peak 670 cm-1 is due to the Î½1-mode of the tetrahedral [CoO4/2]4- units. The calculated values of the magnetic susceptibility from the observed magnetic moments data at 300 K are found to be 10-6 Â emu/gG in S1-S5 which show the weak paramagnetic nature of the materials. Â The EMR lineshapes recorded at 6, 50, 77, and 300 K are very broad, isotropic and smeared out with only two detectable characteristic peaks. The giso-value 2.3 is due to the doped Co2+(3d7) ions in tetrahedral coordinations, while the giso-value 2.01 is due to the doped Nd3+(4f3) ions in distorted octahedral coordinations. The lineshapes only at 6 K are distinct, while at higher temperatures Â these peaks are severely smeared out. The optical absorption broad band at 750 nm (13262 cm-1) is assigned to 4I9/2 Â® 4F7/2 + 4S3/2 transitions in optically active Nd3+(4f3) ions, and theÂ peak 520 nm (19230 cm-1) is attributed to 4A2g Â® 4T1g(P) transitions in Co2+ (S=3/2, 3d7) ions in tetrahedral coordinations.